Spatial distribution of delayed initiation of antenatal care visits and associated factors among reproductive age women in Ethiopia: spatial and multilevel analysis of 2019 mini-demographic and health survey - Adugnaw Zeleke Alem; Fantu Mamo Aragaw; Daniel Gashaneh Belay; Dagmawi Chilot; Melaku Hunie Asratie (BMJ Open)
Objectives This study aimed to assess the spatial distribution, wealth-related inequality and determinants for delayed initiation of antenatal care (ANC) visits among reproductive-age women in Ethiopia.Design Cross-sectional study design.Setting Ethiopia.Participants A total of 2924 reproductive-age women who had given birth in the 5 years preceding the survey.Outcome measure Delayed initiation of ANC visits.Results The magnitude of delayed initiation of ANC visits among reproductive-age women in Ethiopia was 62.63% (95% CI 60.86%, 64.37%). Women aged 35–49 (AOR=1.42; 95% CI 1.04, 1.94), being protestant religion followers (AOR=1.43; 95% CI 1.06, 1.94), being in higher wealth index (AOR=0.53; 95% CI 0.41, 0.69), living in rural residence (AOR=1.50; 95% CI 1.02, 2.19) and living in the metropolitan region (AOR=0.45; 95% CI 0.26, 0.77) were significantly associated with delayed initiation of ANC visit. Southern Nations Nationalities and Peoples Region (SNNPR), Somalia, Benishangul Gumuz, Southern Addis Ababa and Gambella regions were hot spot regions for delayed initiation of ANC visits. The SaTScan analysis result identified 107 primary clusters of delayed initiation of ANC visits located in regions of SNNPR, Gambella, Southern Addis Ababa, Eastern Oromia and Benishangul Gumuz.Conclusions Significant spatial clustering of delayed initiation of ANC visits was observed in Ethiopia. More than half of women had delayed initiation of ANC visits in Ethiopia. Women’s age, religion, wealth index, residence and region were significant predictors of delayed initiation of ANC visits. There is a disproportional pro-poor distribution of delayed initiation of ANC visits in Ethiopia. Therefore, interventions should be designed in the hot spot areas where delayed initiation of ANC visits was high to enhance the timely initiation of ANC visits.